Molecular Diagnosis and Targeting for Thoracic and Gastrointestinal Malignancy (Current Human Cell Research and Applications, 2018)
This volume focuses on the clinical applications of molecular diagnosis and targeted therapy from the viewpoint of oncologists specializing in specific organs. In addition, it discusses the role of molecular diagnosis and targeted therapy in the course of surgical treatment. Recent, rapid advances in molecular biology have shed new light on the mechanisms of cancer progression, and molecularly targeted drugs have been used to treat a variety of malignant diseases. For the diagnosis and precise treatment of cancer, analysis of the molecular background of the tumor is indispensable. However, there are both tumor-specific and comprehensive mechanisms involved in these processes. Accordingly, a firm grasp of molecular diagnosis and targeted therapies for different tumors is vital for clinicians and basic researchers alike. This book provides essential information and the latest findings on molecular diagnosis and targeted therapy for thoracic and gastrointestinal malignancies. Though primarily intended for clinical and basic oncologists, it also offers a useful guide for clinicians who are interested in this field and are considering getting started in molecular diagnosis and targeted therapy.